Partnership in corporate social responsibility program: Indonesia case study - Abidin, Zainal; Gunawan, Sandy (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This current study is a qualitative single case study focusing on the implementation program of the CSR partnership between PT Prudential Life Assurance (PLA) and Institut Kemandirian Dompet Dhuafa Republika (IKDDR) from 2012–2016. Based on purposive sampling, the main respondents in this research are representatives from three institutions: the government, corporations, and Third Sector Organizations (Organisasi et al./OST), as well as beneficiaries from the society. The study finds six conclusions: (1) the partnership of these two institutions is affected by a lack of resources, efficiency pressure, and other innovative program opportunities; (2) partner selection relies on the alignment of the vision, mission, and values of the organization, reputation, experience, and competency of a potential partner; and (3) the main considerations in program formulation are innovation and cost efficiency; (4) the most important aspects in program monitoring and evaluation are performance and punctuality; (5) program impact analysis is obtained from field observation and interview with related institution and (6) decision of the program continuation is on the authority of funder organization.